(untitled) (Research, Society and Development, 2020)
Objective: To analyze the physical and socioeconomic aspects that affect the quality of life of nursing professionals. Methodology: This is a descriptive exploratory research, cross-sectional with qualitative approach, conducted through a semi-structured questionnaire containing open and closed questions that deal with the factors that affect the quality of life of nurses. Data were collected during March and April, where they were analyzed through semi-directional interviews, and transcribed in the text according to the selected classes. Results: The sample consisted of 25 nursing professionals of both sexes. Wage income was shown to range from 1-3 minimum wages (52%), professionals work 30-40hrs (96%) per week, and 20% reported having another job or source of extra income. Conclusion: The level of satisfaction about the nurses’ quality of life was satisfactory, because they work with what they like, and have more affinity, arousing a pleasure to help others, making them feel useful and important. However, it is noteworthy that it is necessary a salary adjustment, reduction of the workload, healthy environments and recognition of nursing professionals.